Gamification and game based learning for vocational education and training: A systematic literature review - Dahalan, Fazlida (Springer, 2024)
Games have been used as a learning tool for centuries. Gamification and game-based learning are becoming more prominent in educational settings for several reasons. When it comes to learning, being focused and immersed can massively improve a student's experience. The purpose of this study is to map the emerging trends of gamification and game-based learning (GBL) in the Vocational and Education Training (VET) sector. For this purpose, a Systematic Literature Review was conducted through the three most relevant scientific databases - Web of Science, Scopus, ScienceDirect, and PubMed with Google Scholar as a supporting database. The obtained sample was further selected following the PRISMA guidelines with screening and eligibility processes conducted based on inclusion criteria that were defined with consideration to the research's aim. This review comprised seventeen studies. The findings revealed a growing interest in the Asian continents in research from 2020 onwards. Furthermore, most of the study is centred on vocational schools and colleges in the engineering and healthcare fields. According to the overview, the digital learning platform and simulation technology are the most promising tools used in the research. The findings support the conclusion that gamification and game-based learning can improve academic performance, engagement, and motivation in vocational education learners. As a result, this study suggests that more research is needed to determine the gamification strategies that are most suited for vocational education and learning.